Ethnomycology and trade channel of Cordyceps sinensis (Berk.) Sacc. in Arunachal Pradesh, North East India - Barman , Alokesh; Shrivastava, Karuna; Singh, Sorokhaibam Sureshkumar (Ethnobotany Research and Applications, 2025)
Background: Cordyceps sinensis a mysterious andnecrotrophic but highly medicinal fungus found naturally dispersed in Himalayan region. It is commonly known like Yartsagunbu, Yarsagumba, Keeda Jadi or Caterpillar fungus. This species is collected from wild and used invarious traditional healing practices thus has attracted herbalists and contemporary researchers both. The purpose of this study was to explore ethnomycological information among ethnic groups, availability, harvesting, trade channel, and marketing of this valuable fungus in Arunachal Pradesh, India. Methods: The survey was conducted among Monpa, Sherdukpen, Memba and Nepali communities residing in three districts of the state located between 3500-5000m altitudes above sea levelthrough semi-structured questionnaire. The quantitative ethnobiological data analysis such as relative frequency of citation and cultural importance index were done following standard methods. Results: The results revealed that C. sinensis is primarily used for treating tumours, inflammation, liver and kidney disorders, diabetes, and as a sexual stimulant and anti-aging agent. The study highlights how this mushroom play crucial role in local health, traditions and rural economies, with prices ranging from 250–400 INR per piece. Despite its significance, the trade remains informal and lacks a structured market. The findings underscore the urgent need for documentation and sustainable harvesting practices to preserve both indigenous knowledge and the ecological future of this valuable resource. Conclusion: This study provides a comprehensive ethnomycological account of Cordyceps sinensis among the high-altitude tribes of Arunachal Pradesh, revealing its vital role in traditional healthcare, cultural practices, and local economies. Keywords: Arunachal Pradesh, Cordyceps sinensis, Market value, Monpa tribe, Traditional knowledge.